Hope Ridings Miller papers - Miller, Hope Ridings
Correspondence, interviews, published writings, invitations, newspaper clippings, and photographs documenting Miller's career as society editor of the Washington Post (1938-1944), associate editor and editor of Diplomat magazine (1952-1966), and author of newspaper columns, articles, and books on social and diplomatic life in Washington, D.C. Includes interviews (1934-1935) conducted by Boyden Sparkes with Evalyn Walsh McLean and correspondence, writings, and photographs relating to Perle Mesta. Other persons represented include Lady Bird Johnson, Lyndon B. Johnson, Sam Rayburn, and Eleanor Roosevelt.
Author, editor, and journalist. Born Hope Ridings; married Clarence Miller in 1932.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Johnson, Lady Bird, -- 1912-2007.; Johnson, Lyndon B. -- 1908-1973.; McLean, Evalyn Walsh, -- 1886-1947.; Mesta, Perle, -- approximately 1890-1975.; Rayburn, Sam, -- 1882-1961.; Roosevelt, Eleanor, -- 1884-1962.; Sparkes, Boyden, -- 1890-1954.; Diplomat (Washington, D.C.); Washington post; American newspapers -- Washington (D.C.); Diplomatic and consular service -- Washington (D.C.); Diplomatic and consular service, American; Journalism -- Washington (D.C.); Periodical editors -- Washington (D.C.); Washington (D.C.) -- Social life and customs; Authors; Editors; Journalists